Comparison of yeast-based estrogen receptor assays - Saito, M (Water science and technology : a journal of the International Association on Water Pollution Research, 2002)
In order to quantitatively compare measurement methods used to evaluate estrogenic activity in environmental samples, 13 substances and sewage samples were measured using three methods that employ recombinant yeast to measure such estrogenic activity. The estrogenic activity of the chemical substances confirmed a correlation between the three measurement methods. Two methods failed to measure estrogenic activity in some of the sewage samples because the yeast growth was inhibited. But the one remaining method was able to estimate the estrogenic activities of all sewage samples without the inhibition of the yeast growth. Similar correlation was observed between the methods for the estrogenic activities of the final discharge that was measured